Risk factors associated with a reduced response in the treatment of erysipelas - Linke, Miriam; Booken, Nina (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Background In most cases, erysipelas may be adequately treated using first-line antibiotic therapy. However, clinicians are sometimes confronted with complicated cases, in which patients do not respond to initial antibiotic therapy. The objective of this study was to identify risk factors associated with a reduced response to antibiotic therapy and, thus, a more complicated disease course. Patients and Methods We retrospectively analyzed the clinical course of 98 patients with erysipelas treated with standard antibiotic therapy. Patient groups showing different therapeutic responses were compared with respect to clinical data, medical history, and laboratory parameters. Results Patients with bullous or hemorrhagic erysipelas (p = 0.0008), stasis dermatitis (p = 0.01) or chronic venous insufficiency (p = 0.0004) showed a significantly reduced response to initial therapy with cefuroxime or clindamycin, respectively. Furthermore, the response to initial therapy significantly depended on C-reactive protein (p = 0.007) and neutrophil (p = 0.02) levels. Conclusion In erysipelas patients with clinical complications, abnormal laboratory parameters or preexisting local skin damage, an intensified antibiotic regimen should be considered.